Illinois Waterfowl Surveys and Investigations W-43-R-67 Annual Progress Report FY2020 - Yetter, Aaron P.; Fournier, Auriel M.V.; Gilbert, A.D.; Osborn, J.M.; Klimas, S.T.; Askren, R.J.; Malanchuk, L.J.; Beach C.R.; Lancaster, Joseph D.; Jacques, C.N.; Hagy, H.M.; and Ward, M.P. (Illinois Natural History Survey, 2020)
We will investigate the ecology, distribution, and abundance of waterfowl and other wetland-associated birds in relation to habitat characteristics along and nearby the Illinois and Mississippi rivers; waterfowl, marsh birds, shorebirds, and other wetland-associated birds in wetlands and deepwater habitats statewide; investigate the ecology and distribution of shorebirds in relation to habitat characteristics in central Illinois and Canada geese in northeastern Illinois; and summarize and distribute our results. 1) Inventory abundance and distribution of waterfowl and other waterbirds (≥10 species and guilds) during autumn (September–January) and spring migration (February–April) at a minimum of 40 sites along and nearby the Illinois and central Mississippi rivers, 2) Evaluate postbreeding ecology of wood ducks by radio-marking up to 100 individuals during late summer and autumn in and nearby the central Illinois River Valley, 3) Investigate movement and population ecology of lesser scaup and canvasback by trapping and leg-banding a minimum of 1,000 individuals during spring migration in the Illinois RiverValley, 4) Continue to investigate the ecology of green-winged teal and gadwall during spring migration in and nearby the central Illinois River Valley, 5) Evaluate waterfowl harvest and hunter success at state-managed waterfowl hunting areas in relation to food abundance and quality on nearby managed sanctuaries in the Illinois River Valley, 6) Investigate movements and home range size of ≥10 Canada geese during winter in and near the Greater Chicago Metropolitan Area (GCMA) of Illinois, 7) Inventory abundance and distribution of shorebirds during spring (April–May) and autumn (July–August) migration at ≥40 sites along the Illinois River, 8) Assist banding crews during August near Yorkton, Saskatchewan, Canada to fulfill duck banding quotas for the Mississippi Flyway Technical Section and Council, and 9) Distribute results and findings to site managers and biologists of the Illinois Department of Natural ...